YOUNG PEOPLE AND FASCISM PROPAGANDA IN IRAN: A CRITICAL ANALYSIS OF THE ANTHEM ‘HAIL COMMANDER’ - Matin, Alireza Azeri (International Journal of Humanity Studies (IJHS), 2024)
Since its inception in 1979, the Islamic Republic of Iran (IRI) has enormously capitalized on exploiting youths, from the recruitment of child soldiers during the Iran-Iraq war to deployments of underage boys and girls for political socialization. Political socialization, in this sense, has involved reinforcing Shia/Revolutionary ideologies through mobilizing young people for various cultural activities and propaganda campaigns. As part of these efforts, and in line with IRI’s mounting domestic and international struggles, since March 2022, the government has heavily invested in propagating ‘Hail Commander’, an anthem produced and broadcast by the state-run media. Exclusively performed by 7-14 years old children in uniforms, the content of this anthem (lyrics and visual features) bears a close resemblance to the lyrics of Giovinezza (Juvenility) of fascist Italy (1924-1943) and the political ideals promoted by Hitlerjugend (Hitler Youth) in Nazi Germany (1926-1945). By drawing on theories of fascism, propaganda, and political socialization, and using comparative critical analysis, this study reveals the underlying propagandist messages in Hail Commander and its relations to the fascist/Nazi praxis and ideologies. It is further argued that the creation of Hail Commander should be seen as the revival of the child soldier phenomenon, albeit in the form of media representation.